PENGARUH KOMPENSASI FINANSIAL, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL PROVINSI SULAWESI TENGAH - Djibran, Latifah Awad (Katalogis, 2017)
The research aims to determine and analyze the influence of financial competency on work discipline of officials in The Agency of population and national family planning of centra sulawesi; determine and analyze the influence of work motivation on work discipline of officials in The Agency of population and national family planning of centra sulawesi; determine and analyze the influence of work discipline on the performance of officials in The agency of population and national family planning of centra sulawesi; determine and analyze the influenceof financial competency on performance of offcial in The agency of population and national family planning of centra sulawesi; determine and analyze the influence of work motivation on the performance of officials in The agency of population and national family planning of centra sulawesi. There were 80 officials involved as respondents in this study. The results show that financial compensation has significant influence on work discipline of official in The agency of population and national family planning of centra sulawesi;work motivation has significant influence on work discipline of officials in The agency of population and national family planning of centra sulawesi; work discipline has significant influence on officials performance in The agency of population and national family planning of centra sulawesi;; financial compensation has significant influence on officials performance in The agency of population and national family planning of centra sulawesi; work motivation has significant influence on officials performance in The agency of population and national family planning of centra sulawesi.